Changes in sea ice influence bowhead whale distribution and overlap with vessel transits in the Pacific Arctic - Angela R. Szesciorka; Justin A. Crawford; Greta Ferloni; Donna D. W. Hauser; Lori Quakenbush; Kathleen M. Stafford (Frontiers in Marine Science, 2026)
Introduction Arctic warming has resulted in substantial decreases in sea ice and a longer open-water season. This is occurring concurrently with changes in Bering-Chukchi-Beaufort bowhead whale seasonal movements and increasing vessel traffic through Bering Strait, which may increase strike risk. Methods To assess vessel traffic relative to bowhead whale distributions before (2013/14–2016/17), during (2017/18), and after (2018/19) a significantly low winter sea ice event in the Pacific Arctic, we combined vessel location data for eight vessel types during six seasons (September–March 2013–2019) transiting through whale utilization distributions (UDs) developed from satellite-linked telemetry from whales tagged during 2008–2019. Results Before the low ice event, the home range (95% UD) and core use area (50% UD) followed a consistent seasonal pattern of bowhead whales migrating south through the Chukchi Sea to wintering areas in the western Bering Sea. The UDs shifted northward during the low ice event, resulting in a decline in annual vessel transits through UDs, from an average of 234 transits in the 95% UD and 139 in the 50% UD during the four seasons before the event to 62 and 45 transits, respectively during the low ice event. Mean vessel speeds, however, increased from 7.2 to 8.7 kt in the 95% UD. After the event, UDs shifted southward, although not as far as before, and transits through UDs remained low (81 and 34) and at similar mean speeds (8.9 and 8.7 kt) than during the event. Discussion Regardless of period, vessels spent the most time along the northern coast of Chukotka and western Bering Sea resulting in the highest vessel densities and fastest mean vessels speeds. While it appears bowhead whales can adjust their distributions to rapidly changing ice conditions consequently overlapping with fewer vessels, faster transits through their UDs could put whales at increased risk of lethal strikes in the future.

Corrigendum to “Differential metal and metalloid contents in fresh and cooked Charu mussels (Mytella charruana) from a southeastern Brazilian estuary and associated human health risks” [Food Control 166 (2024) 110700] - Júlia Vianna de Pinho; Isabel Q. Willmer; Carlos Adam Conte-Junior; Amanda Pontes Lopes; Tatiana D. Saint’Pierre; Everton G.N. dos Santos; Rachel Ann Hauser-Davis (Food Control, 2026)

FOXO3 mediated gene expression modulates doxorubicin sensitivity in human cardiomyocytes - J.G. Faber; M. van Herwijnen; D. Hauser; S. Daemen; F. Caiment; T. van den Beucken (Toxicology, 2025)

Macrofauna accelerates nutrient cycling through litterfall in cocoa agroforestry systems - O. Oyedele; D.-G. J. M. Hougni; S. Hauser; A. G. T. Schut; L. S. Woittiez; L. Rusinamhodzi; M. O. Ogunlade; K. E. Giller (Nutrient Cycling in Agroecosystems, 2025)
This study aimed to better understand nitrogen (N), phosphorus (P), and potassium (K) cycling through litterfall in smallholder cocoa agroforestry systems and to assess if these nutrient flows can be measured using standard litterbags. Annual litter production, relative mass loss, and nutrient loss rates from cocoa leaf litter were evaluated in three farms in south-western Nigeria with and without macrofauna access. Litterfall was measured fortnightly close to the base of the cocoa tree and at the edge of the tree canopies from January 2020 to December 2021. Leaf litter decomposition rates were determined over 388 days in 2 mm mesh litterbags to exclude macrofauna and in frames open to the soil surface to allow macrofauna access. Concentrations of C, N, P, and K were measured in the remaining litter at 180, 244, 314, and 388 days after incubation. Annual estimates of litterfall (10.62 Mg DM ha −1 ) did not significantly differ between the traps close to and away from the cocoa tree trunk. Nutrient cycling from litter was estimated at approximately 101 kg N, 5 kg P, and 89 kg K ha −1 year −1 . Relative litter decomposition rates ( k ) significantly differed between frames and litterbags. Macrofauna access significantly reduced the C:N ratio in the remaining litter and increased N and P loss from the litter layer by 28 and 69%, respectively. In conclusion, nutrient flows through litterfall are considerable, and N and P transfer rates to soil are likely underestimated in litterbag experiments that exclude macrofauna.

Exploring Biases of the Healthy Eating Index and Alternative Healthy Eating Index When Scoring Low-Carbohydrate and Low-Fat Diets - Michelle E. Hauser; Jennifer C. Hartle; Matthew J. Landry; Priya Fielding-Singh; Cynthia W. Shih; FeiFei Qin; Joseph Rigdon; Christopher D. Gardner (Journal of the Academy of Nutrition and Dietetics, 2024)

Differential metal and metalloid contents in fresh and cooked Charu mussels (Mytella charruana) from a southeastern Brazilian estuary and associated human health risks - Júlia Vianna de Pinho; Isabel Q. Willmer; Carlos Adam Conte-Junior; Amanda Pontes Lopes; Tatiana D. Saint’Pierre; Everton G.N. dos Santos; Rachel Ann Hauser-Davis (Food Control, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Towards a Model-Based Interpretation of Measurements of Mineralogical and Chemical Compositions - Juerg Hauser; George D. Miron; Svetlana Kyas; Allan M. M. Leal; James Gunning (Mathematical Geosciences, 2024)
We introduce a new methodology for inference of fluid composition from measurements of mineralogical or chemical compositions, expanding upon the use of reactive transport models to understand hydrothermal alteration processes. The reactive transport models are used to impute a latent variable explanatory mechanism in the formation of hydrothermal alteration zones and mineral deposits. An expectation maximisation algorithm is then employed to solve the joint problem of identifying alteration zones in the measured data and estimating the fluid composition, based on the fit between the mineral abundances in the measured and predicted alteration zones. Using the hydrothermal alteration of granite as a test case (greisenisation), a range of synthetic tests is presented to illustrate how the methodology enables objective inference of the mineralising fluid. For field data from the East Kemptville tin deposit in Nova Scotia, the technique generates inferences for the fluid composition which compare favourably with previous independent estimates, demonstrating the feasibility of the proposed calibration methodology.

Multiple Ecological Axes Drive Molecular Evolution of Cone Opsins in Beloniform Fishes - Katherine D. Chau; Frances E. Hauser; Alexander Van Nynatten; Jacob M. Daane; Matthew P. Harris; Belinda S. W. Chang; Nathan R. Lovejoy (Journal of Molecular Evolution, 2024)

Aligning theoretical and empirical representations of soil carbon-to-nitrogen stoichiometry with process-based terrestrial biogeochemistry models - Katherine S. Rocci; Cory C. Cleveland; Brooke A. Eastman; Katerina Georgiou; A. Stuart Grandy; Melannie D. Hartman; Emma Hauser; Hannah Holland-Moritz; Emily Kyker-Snowman; Derek Pierson; Peter B. Reich; Else P. Schlerman; et al. (Soil Biology and Biochemistry, 2024)

First metal and metalloid study assessment for the Black Triggerfish Melichthys niger (Bloch, 1786): Baseline data from a pristine South Atlantic oceanic island - Rachel Ann Hauser-Davis; Isabella C. Bordon; Isabel Q. Willmer; Amanda P. Lopes; Sérgio C. Moreira; Tatiana D. Saint'Pierre; Marcelo Vianna (Marine Pollution Bulletin, 2023)

Predation on ringed seals in subnivean lairs in northwest Alaska during spring 1983 and 1984 - Donna D. W. Hauser; Kathryn J. Frost; John J. Burns (Marine Mammal Science, 2023)

The relevance of pedigrees in the conservation genomics era - Stephanie J. Galla; Liz Brown; Yvette Couch‐Lewis (Ngāi Tahu: Te Hapū o Ngāti Wheke, Ngāti Waewae); Ilina Cubrinovska; Daryl Eason; Rebecca M. Gooley; Jill A. Hamilton; Julie A. Heath; Samantha S. Hauser; Emily K. Latch; Marjorie D. Matocq; Anne Richardson; et al. (Molecular Ecology, 2022)
Over the past 50 years conservation genetics has developed a substantive toolbox to inform species management. One of the most long‐standing tools available to manage genetics—the pedigree—has been widely used to characterize diversity and maximize evolutionary potential in threatened populations. Now, with the ability to use high throughput sequencing to estimate relatedness, inbreeding, and genome‐wide functional diversity, some have asked whether it is warranted for conservation biologists to continue collecting and collating pedigrees for species management. In this perspective, we argue that pedigrees remain a relevant tool, and when combined with genomic data, create an invaluable resource for conservation genomic management. Genomic data can address pedigree pitfalls (e.g., founder relatedness, missing data, uncertainty), and in return robust pedigrees allow for more nuanced research design, including well‐informed sampling strategies and quantitative analyses (e.g., heritability, linkage) to better inform genomic inquiry. We further contend that building and maintaining pedigrees provides an opportunity to strengthen trusted relationships among conservation researchers, practitioners, Indigenous Peoples, and Local Communities.

Metal and Metalloid Contamination in Green Sea Turtles (Chelonia mydas) Found Stranded in Southeastern Brazil - Daphne de Albuquerque Bruno; Isabel Q. Willmer; Lucia Helena S. de S. Pereira; Rafael C. C. Rocha; Tatiana D. Saint’Pierre; Paula Baldassin; Ana Carolina S. Scarelli; Amanda Dias Tadeu; Fábio V. Correia; Enrico M. Saggioro; Leila S. Lemos; Salvatore Siciliano; et al. (Frontiers in Marine Science, 2021)
Sea turtles tend to accumulate high metal levels in their tissues and are considered excellent pollution bioindicators. Studies concerning metal contamination in hatchlings, however, are non-existent for one of the most abundant species in Brazil, green sea turtles, while several other metal assessments in juvenile muscles are still scarce. In this context, this study aimed to analyze the concentrations of 12 elements in kidney and muscle samples from green sea turtles ( Chelonia mydas ; n = 24) found stranded in Rio de Janeiro, southeastern Brazil. Elemental concentrations were determined by inductively coupled plasma mass spectrometry (ICP-MS). The presence of fibropapillomatosis, an increasingly common disease in sea turtles which has been associated to metal contamination, was also evaluated. Most elements (Mn, Fe, Co, Ni, Cu, Zn, Cd, Hg, and Pb) were significantly higher in liver, while Al and As were significantly higher in muscle tissue, indicating bioaccumulation of the latter two elements. No differences between juvenile male and female green turtles were observed for either liver or kidney concerning the investigated elements. Literature comparisons of studies conducted in other areas throughout the Brazilian coast indicate higher concentrations of Cd, Mn, As, Hg, and Zn in kidneys, of probable anthropogenic origin. Several statistically significant inter-elemental correlations were observed between toxic elements, indicating similar sources for these environmental contaminants. Significant correlations between Hg in muscle and kidney and As in the same organs suggest bioaccumulation of both elements in muscle. Three individuals assessed herein exhibited fibropapillomatosis, and further assessments in this regard and potential correlations to the detected metal concentrations are currently being carried out. In addition, evaluations concerning other toxic compounds, as well as deleterious cellular effects, are also underway, since total metal concentrations do not reflect total elemental bioavailability.

Cytosolic and Metallothionein-Bound Hepatic Metals and Detoxification in a Sentinel Teleost, Dules auriga, from Southern Rio de Janeiro, Brazil - R. A. Hauser-Davis; D. R. Silva-Junior; A. R. Linde-Arias; M. Vianna (Biological Trace Element Research, 2021)

Metal-Associated Biomarker Responses in Crabs from a Marine Protected Area in Southeastern Brazil - G. S. Araujo; P. K. Gusso-Choueri; D. I. T. Favaro; R. C. C. Rocha; T. D. Saint’Pierre; R. A. Hauser-Davis; B. Braz; R. E. Santelli; A. S. Freire; W. T. V. Machado; A. C. F. Cruz; D. M. S. Abessa (Archives of Environmental Contamination and Toxicology, 2020)

Understanding the Scientific Basis of Post-traumatic Stress Disorder (PTSD): Precision Behavioral Management Overrides Stigmatization - Kenneth Blum; M. C. Gondré-Lewis; E. J. Modestino; L. Lott; D. Baron; D. Siwicki; T. McLaughlin; A. Howeedy; M. H. Krengel; M. Oscar-Berman; P. K. Thanos; I. Elman; et al. (Molecular Neurobiology, 2019)

Hepatic Metal and Metallothionein Levels in a Potential Sentinel Teleost, Dulesauriga, from a Southeastern Brazilian Estuary - R. A. Hauser-Davis; D. R. Silva-Junior; A. R. Linde-Arias; M. Vianna (Bulletin of Environmental Contamination and Toxicology, 2019)

HIV-1 Tat and opioids act independently to limit antiretroviral brain concentrations and reduce blood–brain barrier integrity - Crystal R. Leibrand; Jason J. Paris; Austin M. Jones; Quamrun N. Masuda; Matthew S. Halquist; Woong-Ki Kim; Pamela E. Knapp; Angela D. M. Kashuba; Kurt F. Hauser; MaryPeace McRae (Journal of NeuroVirology, 2019)

Genome-wide association study of primary open-angle glaucoma in continental and admixed African populations - Pieter W. M. Bonnemaijer; Adriana I. Iglesias; Girish N. Nadkarni; Anna J. Sanyiwa; Hassan G. Hassan; Colin Cook; Mark Simcoe; Kent D. Taylor; Claudia Schurmann; Gillian M. Belbin; Eimear E. Kenny; Erwin P. Bottinger; et al. (Human Genetics, 2018)

Migratory interchange of humpback whales (Megaptera novaeangliae) among breeding grounds of Oceania and connections to Antarctic feeding areas based on genotype matching - D. Steel; M. Anderson; C. Garrigue; C. Olavarría; S. Caballero; S. Childerhouse; P. Clapham; R. Constantine; S. Dawson; M. Donoghue; L. Flórez-González; N. Gibbs; et al. (Polar Biology, 2018)

Optimal schedule for monitoring a plant incursion when detection and treatment success vary over time - Mathieu Bonneau; Cindy E. Hauser; Nicholas S. G. Williams; Roger D. Cousens (Biological Invasions, 2018)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Decadal shifts in autumn migration timing by Pacific Arctic beluga whales are related to delayed annual sea ice formation - Donna D. W. Hauser; Kristin L. Laidre; Kathleen M. Stafford; Harry L. Stern; Robert S. Suydam; Pierre R. Richard (Global Change Biology, 2017)
Migrations are often influenced by seasonal environmental gradients that are increasingly being altered by climate change. The consequences of rapid changes in Arctic sea ice have the potential to affect migrations of a number of marine species whose timing is temporally matched to seasonal sea ice cover. This topic has not been investigated for Pacific Arctic beluga whales ( Delphinapterus leucas ) that follow matrilineally maintained autumn migrations in the waters around Alaska and Russia. For the sympatric Eastern Chukchi Sea (‘Chukchi’) and Eastern Beaufort Sea (‘Beaufort’) beluga populations, we examined changes in autumn migration timing as related to delayed regional sea ice freeze‐up since the 1990s, using two independent data sources (satellite telemetry data and passive acoustics) for both populations. We compared dates of migration between ‘early’ (1993–2002) and ‘late’ (2004–2012) tagging periods. During the late tagging period, Chukchi belugas had significantly delayed migrations (by 2 to >4 weeks, depending on location) from the Beaufort and Chukchi seas. Spatial analyses also revealed that departure from Beaufort Sea foraging regions by Chukchi whales was postponed in the late period. Chukchi beluga autumn migration timing occurred significantly later as regional sea ice freeze‐up timing became later in the Beaufort, Chukchi, and Bering seas. In contrast, Beaufort belugas did not shift migration timing between periods, nor was migration timing related to freeze‐up timing, other than for southward migration at the Bering Strait. Passive acoustic data from 2008 to 2014 provided independent and supplementary support for delayed migration from the Beaufort Sea (4 day yr −1 ) by Chukchi belugas. Here, we report the first phenological study examining beluga whale migrations within the context of their rapidly transforming Pacific Arctic ecosystem, suggesting flexible responses that may enable their persistence yet also complicate predictions of how belugas may fare in the future.

HIV-1 Tat causes cognitive deficits and selective loss of parvalbumin, somatostatin, and neuronal nitric oxide synthase expressing hippocampal CA1 interneuron subpopulations - William D. Marks; Jason J. Paris; Christina J. Schier; Melissa D. Denton; Sylvia Fitting; A. Rory McQuiston; Pamela E. Knapp; Kurt F. Hauser (Journal of NeuroVirology, 2016)

Subtle genetic population structure in Pacific halibut Hippoglossus stenolepis - D. P. Drinan; H. M. Galindo; T. Loher; L. Hauser (Journal of Fish Biology, 2016)
Pacific halibut Hippoglossus stenolepis from 10 sampling locations throughout their range were investigated for signs of population structure. Two genetic data sets were created: (1) all individuals ( n = 828) at few anonymous microsatellite markers (number of loci = 16); (2) fewer individuals ( n = 435) genotyped at anonymous as well as expressed sequence‐tag linked microsatellites (number of loci = 61). A combination of multidimensional scaling plots, discriminant analysis of principal components and pairwise differentiation estimates suggested that samples from the Aleutian Islands, particularly the western Aleutian Islands, were genetically distinct from samples collected in other regions. In addition, outlier analyses found that two markers linked to expressed sequence tags may be under directional selection and could explain the differentiation among samples. These results confirm findings from previous research and suggest that population structure may exist within a current management unit ( i.e. International Pacific Halibut Commission Regulatory Area 4B ).

An environmental forensic approach for tropical estuaries based on metal bioaccumulation in tissues of Callinectes danae - Isabella C. A. C. Bordon; Jorge E. S. Sarkis; Nathalia P. Andrade; Marcos A. Hortellani; Deborah I. T. Favaro; Mauricio H. Kakazu; Marycel E. B. Cotrim; Raquel T. Lavradas; Isabel Moreira; Tatiana D. Saint’Pierre; Rachel Ann Hauser-Davis (Ecotoxicology, 2016)

Disciplinary reporting affects the interpretation of climate change impacts in global oceans - Donna D. W. Hauser; Elizabeth D. Tobin; Kirsten M. Feifel; Vega Shah; Diana M. Pietri (Global Change Biology, 2016)
Climate change is affecting marine ecosystems, but different investigative approaches in physical, chemical, and biological disciplines may influence interpretations of climate‐driven changes in the ocean. Here, we review the ocean change literature from 2007 to 2012 based on 461 of the most highly cited studies in physical and chemical oceanography and three biological subdisciplines. Using highly cited studies, we focus on research that has shaped recent discourse on climate‐driven ocean change. Our review identified significant differences in spatial and temporal scales of investigation among disciplines. Physical/chemical studies had a median duration of 29 years ( n = 150) and covered the greatest study areas (median 1.41 × 10 7 km 2 , n = 148). Few biological studies were conducted over similar spatial and temporal scales (median 8 years, n = 215; median 302 km 2 , n = 196), suggesting a more limited ability to separate climate‐related responses from natural variability. We linked physical/chemical and biological disciplines by tracking studies examining biological responses to changing ocean conditions. Of the 545 biological responses recorded, a single physical or chemical stressor was usually implicated as the cause (59%), with temperature as the most common primary stressor (44%). The most frequently studied biological responses were changes in physiology (31%) and population abundance (30%). Differences in disciplinary studies, as identified in this review, can ultimately influence how researchers interpret climate‐related impacts in marine systems. We identified research gaps and the need for more discourse in (1) the Indian and other Southern Hemisphere ocean basins; (2) research themes such as archaea, bacteria, viruses, mangroves, turtles, and ocean acidification; (3) physical and chemical stressors such as dissolved oxygen, salinity, and upwelling; and (4) adaptive responses of marine organisms to climate‐driven ocean change. Our findings reveal that highly cited biological studies are rarely conducted on scales that match those of physical and chemical studies. Rather, we suggest a need for measuring responses at biologically relevant scales.

Complete Genome Sequence of Geobacillus strain Y4.1MC1, a Novel CO-Utilizing Geobacillus thermoglucosidasius Strain Isolated from Bath Hot Spring in Yellowstone National Park - Phillip Brumm; Miriam L. Land; Loren J. Hauser; Cynthia D. Jeffries; Yun-Juan Chang; David A. Mead (BioEnergy Research, 2015)

Population-specific home ranges and migration timing of Pacific Arctic beluga whales (Delphinapterus leucas) - Donna D. W. Hauser; Kristin L. Laidre; Robert S. Suydam; Pierre R. Richard (Polar Biology, 2014)

Fine-scale sampling reveals distinct isolation by distance patterns in chum salmon (Oncorhynchus keta) populations occupying a glacially dynamic environment - E. L. Petrou; J. E. Seeb; L. Hauser; M. J. Witteveen; W. D. Templin; L. W. Seeb (Conservation Genetics, 2014)

Gene–smoking interactions in multiple Rho-GTPase pathway genes in an early-onset coronary artery disease cohort - Cavin Ward-Caviness; Carol Haynes; Colette Blach; Elaine Dowdy; Simon G. Gregory; Svati H. Shah; Benjamin D. Horne; William E. Kraus; Elizabeth R. Hauser (Human Genetics, 2013)

Secondary contact and changes in coastal habitat availability influence the nonequilibrium population structure of a salmonid ( O ncorhynchus keta ) - E. L. Petrou; L. Hauser; R. S. Waples; J. E. Seeb; W. D. Templin; D. Gomez‐Uchida; L. W. Seeb (Molecular Ecology, 2013)
Numerous empirical studies have reported lack of migration–drift equilibrium in wild populations. Determining the causes of nonequilibrium population structure is challenging because different evolutionary processes acting at a variety of spatiotemporal scales can produce similar patterns. Studies of contemporary populations in northern latitudes suggest that nonequilibrium population structure is probably caused by recent colonization of the region after the last P leistocene ice age ended ~13 000 years ago. The chum salmon's ( O ncorhynchus keta ) range was fragmented by dramatic environmental changes during the P leistocene. We investigated the population structure of chum salmon on the N orth A laska P eninsula ( NAP ) and, using both empirical data and simulations, evaluated the effects of colonization timing and founder population heterogeneity on patterns of genetic differentiation. We screened 161 single nucleotide polymorphisms and found evidence of nonequilibrium population structure when the slope of the isolation‐by‐distance relationship was examined at incremental spatial scales. In addition, simulations suggested that this pattern closely matched models of recent colonization of the NAP by secondary contact. Our results agree with geological and archaeological data indicating that the NAP was a dynamic landscape that may have been more recently colonized than during the last deglaciation because of dramatic changes in coastal hydrology over the last several thousand years.

Effective induction of cells expressing GABAergic neuronal markers from mouse embryonic stem cell - Masaki Nishikawa; Naomi Yanagawa; Shunsuke Yuri; Peter Hauser; Oak D. Jo; Norimoto Yanagawa (In Vitro Cellular & Developmental Biology - Animal, 2013)

Killer whales ( Orcinus orca ) in the Canadian Arctic: Distribution, prey items, group sizes, and seasonality - Jeff W. Higdon; Donna D. W. Hauser; Steven H. Ferguson (Marine Mammal Science, 2012)
Killer whales ( Orcinus orca ) have a global distribution, but many high‐latitude populations are not well studied. We provide a comprehensive review of the history and ecology of killer whales in the Canadian Arctic, for which there has previously been little information. We compiled a database of 450 sightings spanning over 15 decades (1850–2008) to document the historical occurrence, distribution, feeding ecology, and seasonality of killer whales observed throughout the region. Sighting reports per decade increased substantially since 1850 and were most frequent in the eastern Canadian Arctic. The mean reported group size was 8.3 (median = 4, range 1–100), but size varied significantly among regions and observed prey types. Observations of predation events indicate that Canadian Arctic killer whales prey upon other marine mammals. Monodontids were the most frequently observed prey items, followed by bowhead whales ( Balaena mysticetus ), phocids, and groups of mixed mammal prey. No killer whale sightings occurred during winter, with sightings gradually increasing from early spring to a peak in summer, after which sightings gradually decreased. Our results suggest that killer whales are established, at least seasonally, throughout the Canadian Arctic, and we discuss potential ecological implications of increased presence with declining sea ice extent and duration.

Marine mammal and seabird summer distribution and abundance in the fjords of northeast Cumberland Sound of Baffin Island, Nunavut, Canada - Kristen M. Diemer; Michael J. Conroy; Steven H. Ferguson; Donna D. W. Hauser; Alice Grgicak-Mannion; Aaron T. Fisk (Polar Biology, 2011)

Innovative coconut-opening in a semi free-ranging rhesus monkey (Macaca mulatta): a case report on behavioral propensities - Jordan A. Comins; Brian E. Russ; Kelley A. Humbert; Marc D. Hauser (Journal of Ethology, 2011)

The variability of processes involved in transgene dispersal—case studies from Brassica and related genera - Rikke Bagger Jørgensen; Thure Hauser; Tina D’Hertefeldt; Naja Steen Andersen; Danny Hooftman (Environmental Science and Pollution Research, 2009)

Spontaneous gene flow and population structure in wild and cultivated chicory, Cichorium intybus L. - L. P. Kiær; F. Felber; A. Flavell; R. Guadagnuolo; D. Guiatti; T. P. Hauser; A. M. Olivieri; I. Scotti; N. Syed; M. Vischi; C. van de Wiel; R. B. Jørgensen (Genetic Resources and Crop Evolution, 2009)

Susceptibility of wild carrot (Daucus carota ssp. carota) to Sclerotinia sclerotiorum - B. D. Jensen; M. R. Finckh; L. Munk; T. P. Hauser (European Journal of Plant Pathology, 2008)

Validation of operational AVHRR subpixel snow retrievals over the European Alps based on ASTER data - N. Foppa; A. Hauser; D. Oesch; S. Wunderle; R. Meister (International Journal of Remote Sensing, 2007)

Changes in open-field activity and novelty-seeking behavior in periadolescent rats neonatally treated with monosodium glutamate - P. Kiss; D. Hauser; A. Tamas; A. Lubics; B. Racz; Z. Horvath; J. Farkas; F. Zimmermann; A. Stepien; I. Lengvari; D. Reglodi (Neurotoxicity Research, 2007)

Hierarchical population genetic structure in the commercially exploited shrimp Crangon crangon identified by AFLP analysis - D. Weetman; A. Ruggiero; S. Mariani; P. W. Shaw; A. R. Lawler; L. Hauser (Marine Biology, 2007)

Tracking silence: adjusting vocal production to avoid acoustic interference - S. E. Roian Egnor; Jeanette Graham Wickelgren; Marc D. Hauser (Journal of Comparative Physiology A, 2007)

Inheritance of Lysosomal Acid β-Galactosidase Activity and Gangliosides in Crosses of DBA/2J and Knockout Mice - Eric C. Hauser; Julie L. Kasperzyk; Alessandra d'Azzo; Thomas N. Seyfried (Biochemical Genetics, 2004)

Measuring and modelling plant area index in beech stands - T. Holst; S. Hauser; A. Kirchgner; A. Matzarakis; H. Mayer; D. Schindler (International Journal of Biometeorology, 2004)

Multiple acoustic features underlie vocal signal recognition in tamarins: antiphonal calling experiments - C. T. Miller; M. D. Hauser (Journal of Comparative Physiology A, 2004)

Periprosthetic modelling of femoral component fit using computed tomography data for total hip arthroplasty: A feasibility study - D. A. Hauser-Kara; D. L. Bartel (Medical & Biological Engineering & Computing, 2002)

Book review - Ruth Tincoff; Marc D. Hauser (Primates, 2002)

CC-chemokine receptor 5 polymorphism and age of onset in familial multiple sclerosis - L. F. Barcellos; A. M. Schito; J. B. Rimmler; E. Vittinghoff; A. Shih; R. Lincoln; S. Callier; M. K. Elkins; D. E. Goodkin; J. L. Haines; M. A. Pericak-Vance; S. L. Hauser; et al. (Immunogenetics, 2000)

Potential tumour doubling time: determination of Tpot for various canine and feline tumours - U. Schwyn; N.E.A. Crompton; H. Blattmann; B. Hauser; B. Klink; A. Parvis; D. Ruslander; B. Kaser-Hotz (Veterinary Research Communications, 1998)

Spatial and temporal gradients of earthworm casting activity in alley cropping systems - S. Hauser*; D. O. Asawalam; B. Vanlauwe (Agroforestry Systems, 1998)

Synaptic differentiation: the role of agrin in the formation and maintenance of the neuromuscular junction - A. J. Denzer; D. M. Hauser; M. Gesemann; M. A. Ruegg (Cell and Tissue Research, 1997)

Male responsiveness to infant distress calls in free-ranging vervet monkeys - Marc D. Hauser (Behavioral Ecology and Sociobiology, 1986)